MODERN METHODS OF TEACHING ENGLISH LANGUAGE - Eshdavlatova Hafiza (Western European Studies, 2025)
This article provides a comprehensive analysis of modern pedagogical methods, technologies, and approaches used in teaching English. Methods such as the communicative approach, interactive techniques, digital technologies, project-based learning, and individualized instruction play a crucial role in enhancing the effectiveness of the educational process. The article offers practical recommendations for teachers, methodologists, and education specialists on implementing innovative pedagogical approaches
Keywords: English language; modern methods; communicative approach